Proceso de atención de enfermería en paciente escolar con apendicitis aguda. - Morocho Suarez, Byron Alexander (2021)
The present work leads to the creation of a clinical case with a selected topic of a pediatric patient with acute appendicitis. This case is presented frequently at the Venus de Valdivia Health Center in The Santa Elena City, La Libertad parish in the area of Pediatrics. For this clinical case, a methodology was carried out where the patient's clinical history, general habits, monitoring of health personnel for their improvement and incorporated into their daily life were known. Likewise, a theoretical framework is deepened where the information about acute appendicitis that different authors tell us is investigated. Acute appendicitis is and will continue to be a frequent pathology in pediatric patients and one of the main causes of hospital admission to a health unit. Acute appendicitis in a pediatric patient is accompanied by symptoms such as nausea, vomiting, hyperthermia of 38 ° C, cramping abdominal pain in the right iliac fossa that requires immediate surgical intervention (appendectomy) for the prompt recovery of the patient.